1992
DOI: 10.1038/359848a0
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte accumulation promoting fibrin deposition is mediated in vivo by P-selectin on adherent platelets

Abstract: The glycoprotein P-selectin is a cell adhesion molecule of stimulated platelets and endothelial cells, which mediates the interaction of these cells with neutrophils and monocytes. It is a membrane component of cell storage granules, and is a member of the selectin family which includes E-selectin and L-selectin. P-selectin recognizes both lineage-specific carbohydrate ligands on monocytes and neutrophils, including the Lewis x antigen, sialic acid, and a protein component. In inflammation and thrombosis, P-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
432
1
9

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 767 publications
(456 citation statements)
references
References 20 publications
14
432
1
9
Order By: Relevance
“…These interactions can result in the development of a more stable platelet‐leukocyte complex as well as promoting the adhesion and recruitment of leukocytes to the endothelium. Recruitment of leukocytes to damaged endothelium by P‐selectin and the generation of leukocyte‐derived microparticles mediate the generation of fibrin 31. Studies in P‐selectin knockout mice showed prolonged bleeding times and increased hemorrhage in response to trauma, providing further evidence for the role of this selectin in hemostasis 32.…”
Section: Discussionmentioning
confidence: 97%
“…These interactions can result in the development of a more stable platelet‐leukocyte complex as well as promoting the adhesion and recruitment of leukocytes to the endothelium. Recruitment of leukocytes to damaged endothelium by P‐selectin and the generation of leukocyte‐derived microparticles mediate the generation of fibrin 31. Studies in P‐selectin knockout mice showed prolonged bleeding times and increased hemorrhage in response to trauma, providing further evidence for the role of this selectin in hemostasis 32.…”
Section: Discussionmentioning
confidence: 97%
“…Several vessels contained entrapped blood cells (eg, see venules in Figure 3A or the small microvessel in Figure 3E), possibly reflecting polymorphonuclear response (indicated by positive staining for polymorphonuclear markers; not shown) as reported previously. 27 Fibrin deposits and fibrin-rich thrombi were found occasionally after 24 hours of reperfusion in tPAϩ/ϩ wild-type 129/Sv and C57BL/6 mice in some venules, but most capillaries and other microvessels were negative for fibrin ( Figures 3G and 3H). Quantitative Western blot analysis for fibrin on 1-mm-thick TTC brain sections confirmed the immunohistological observations by demonstrating significant fibrin deposition in ischemic brain areas in tPAϪ/Ϫ mice versus barely detectable levels of fibrin in tPAϩ/ϩ wild-type control mixed-strain mice ( Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20] Fibrin deposition in ischemic brain can be precipitated by procoagulant transformation of brain microvascular endothelium, [21][22][23]25 formation of a platelet plug, or leukocyte-endothelial interactions during reperfusion. 27 Previous studies have established a link between ischemic brain injury and reduced antithrombotic mechanisms in brain microcirculation in the presence of major stroke risk factors. 23,34,35 In humans, the antithrombotic factor protein C is protective in ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a similar multistep model may apply to the highly efficient accumulation of PMN on surface-adherent platelets under flow. Indeed, rolling and arrest of PMN on activated platelets under flow requires the action of P-selectin and β 2 integrins, respectively (34)(35)(36)(37). Fibrinogen, a Mac-1 ligand (38, 39) which can bind to activated platelets via αIIbβ3 (40), has been implicated in platelet-PMN interactions in cell suspension or whole blood (41).…”
Section: Involvement Of Platelet-activating Factor (Paf) and Leukotrimentioning
confidence: 99%